2020
DOI: 10.1111/jfbc.13382
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chard on brain damage in valproic acid‐induced toxicity

Abstract: Valproic acid or valproate (VPA; 2-propyl valeric acid)-a branched chain carboxylic acid-is the most commonly used as anticonvulsant medication due to its broad effect on several categories of seizure (Duncan, Sander, Sisodiya, & Walker, 2006). Also, it acts as mood stabilizer, therefore, recommended for borderline personality disorder, schizoaffective disorders, social phobias, bipolar disorders, schizophrenia, and impulse disorders (Haddad, Das, Ashfaq, & Wieck, 2009). Besides the positive effects, there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…[ 29 ] We observed reduced GSH levels in brain samples of VPA administered group. In parallel to our findings, Chaudhary and Parvez [ 30 ] and Tunali et al [ 31 ] reported diminished GSH levels in their studies. These negative changes in GSH levels may be explained by the ROS elevating effect of VPA.…”
Section: Discussionsupporting
confidence: 92%
“…[ 29 ] We observed reduced GSH levels in brain samples of VPA administered group. In parallel to our findings, Chaudhary and Parvez [ 30 ] and Tunali et al [ 31 ] reported diminished GSH levels in their studies. These negative changes in GSH levels may be explained by the ROS elevating effect of VPA.…”
Section: Discussionsupporting
confidence: 92%
“…An increased XO activity and elevated PC levels may be the result of the toxic mechanism of VPA triggering oxidative stress in the lungs. [60,82] This may be due to oxidative stress, which could provoke activation of NF-κB that is a major inducer for classically activated proinflammatory macrophages, and COX-2 which regulates proinflammatory eicosanoids formation by promoting lung inflammation. [25] These results were consistent with previously published articles.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are various studies examining the effect of chard and parsley on the brain tissue of control group animals, but the BM has not been studied (Allam et al, 2016; Maodaa et al, 2016; Tunali et al, 2020). Thus, in the present study, we designed only the control + BM group to minimize animal use.…”
Section: Discussionmentioning
confidence: 99%